Formal Development of a Network-Centric RTOS Software Engineering for Reliable Embedded Systems - Verhulst, Eric; Boute, Raymond T.; Faria, José Miguel Sampaio; Saputh, Bernhard H.C; Mezhuyev, Vitaliy (Springer US Imprint: Springer, 2011)
This book describes a formally developed, network-centric Real-Time Operating System, OpenComRTOS. One of the first in its kind, OpenComRTOS was originally developed to verify the usefulness of formal methods in the context of embedded software engineering. Using the formal methods described in this book produces results that are more reliable and higher performance. This methodology is unique because it covers the full range of product development, from requirements and specifications to the final execution platform. It is compatible with safety related engineering standards, such as IEC61508. Uses formal methods to develop Network-centric Real-time Operating Systems Unified Semantics provides a solid base for model driven systems development and can be tuned to an application-specific, concurrent programming paradigm Methods presented enable model-driven, high-reliability, high-performance software & systems engineering Compatible with International Electrotechnical Commission (IEC) 61508, the standard governing functional safety of programmable electronic systems.